Respon ASEAN Terhadap Mundurnya India Dari Kerja Sama Regional Comprehensive Economic Partnership (RCEP) - Raden Maisa Yudono, Wiwiek Rukmi Dwi Astuti, M. Chairil Akbar Setiawan (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
Regional Comprehensive Economic Partnership (RCEP) is a cooperation framework formulated by ASEAN and 6 strategic partner countries and is the first proposal in ASEAN history to discuss comprehensive economic cooperation. RCEP is ASEAN's effort to strengthen its position as regional aktor in the Southeast Asian.  RCEP negotiations underwent changes during India's decision to withdraw from the RCEP negotiations, which prompted ASEAN to respond to these developments. This study fokuses on response taken by ASEAN to India's decision to withdraw from the RCEP negotiations. The concept used is soft regionalism which emphasizes geographic proximity, historical relations and the comparative advantage of the region. Soft regionalism is driven by not only by economic and business interests, but also market interests that become the energy of soft regionalism in Asia. This concept is functioning well because it conforms to the pragmatic Asian political conditions. The findings of this study is that ASEAN cannot be separated from the concept of soft regionalism in which it has been running, and still sees all changes through static point of view. ASEAN needs to make new breakthroughs in realizing comprehensive cooperation in the region.